GAMBARAN PENEGAKAN DIAGNOSIS DAN TATALAKSANA BERDASARKAN TINGKAT KEJADIAN TUMOR PARU DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2018-2021 - Vega Edelweis Veilana; Fransisca Tarida Yuniar Sinaga; Jordy Oktobiannobel; Retno Ariza Soeprihatini Soemarwoto (Medula, 2022)
Tumors that occur in the lungs can be divided into several types, namely benign tumors, malignant tumors, primary tumors and tumors caused by metastases from malignancies originating from other organs. There are about 1 million deaths in the population each year, which are caused by lung cancer malignancies. The case of lung tumor malignancy is ranked 4th, from the total number of cancers that occur in Indonesia. The increase in mortality due to malignant lung tumors is most likely due to delays in diagnosis. According to the Ministry of Health of the Republic of Indonesia, lung tumors are the main cause of death in men with a percentage (21.8%) and in women with a percentage (9.1%). This research uses descriptive observational method with retrospective observation using purposive sampling technique. The data used in the form of medical records. There were 159 lung tumor patients studied, consisting of 77.4% of men, 44.0% of 41-60 years of age, 95.0% of no family history, 67.9% of shortness of breath, and 67.9% of smoking history. 79.2%, using FNAB as much as 37.7%, stage IVA as much as 25.8%, squamosa cell carcinoma as much as 50.3% and chemotherapy as much as 47.8%. Lung tumor patients were mostly found in men, with an age range of 41-60 years, tended to suffer from patients who did not have a family history, the most had symptoms of shortness of breath, were active smokers, the most were stage IVA, with the type of squamous cell carcinoma. FNAB samples were 50.3% and underwent chemotherapy.